The language of salvation : discovering the riches of what it means to be saved - Kuligin, Victor, 1964- (Wooster, OH : Weaver Book Company, 2015)
"A study that explains thirteen different biblical terms which together convey the richness of a single concept: salvation. The book addresses human sin, considers various ideas and convictions of people inside and outside the church, and explores how each of these facets of Christian salvation helps with sharing the gospel"--
Includes bibliographical references and index.
Keywords: Salvation -- Christianity; Salvation -- Christianity -- Terminology